A new microfluidic approach for the one-step capture, amplification and label-free quantification of bacteria from raw samples. Issue 2 (19th October 2016) - Pereiro, Iago; Bendali, Amel; Tabnaoui, Sanae; Alexandre, Lucile; Srbova, Jana; Bilkova, Zuzana; Deegan, Shane; Joshi, Lokesh; Viovy, Jean-Louis; Malaquin, Laurent; Dupuy, Bruno; Descroix, Stéphanie
Abstract : A microfluidic fluidized bed composed of antibody-grafted magnetic beads for the fast visual detection of bacteria by in situ expansion phenomena. Abstract : A microfluidic method to specifically capture and detect infectious bacteria based on immunorecognition and proliferative power is presented. It involves a microscale fluidized bed in which magnetic and drag forces are balanced to retain antibody-functionalized superparamagnetic beads in a chamber during sample perfusion. Captured cells are then cultivated in situ by infusing nutritionally-rich medium. The system was validated by the direct one-step detection of Salmonella Typhimurium in undiluted unskimmed milk, without pre-treatment. The growth of bacteria induces an expansion of the fluidized bed, mainly due to the volume occupied by the newly formed bacteria. This expansion can be observed with the naked eye, providing simple low-cost detection of only a few bacteria and in a few hours. The time to expansion can also be measured with a low-cost camera, allowing quantitative detection down to 4 cfu (colony forming unit), with a dynamic range of 100 to 10 7 cfu ml −1 in 2 to 8 hours, depending on the initial concentration. This mode of operation is an equivalent of quantitative PCR, with which it shares a high dynamic range and outstanding sensitivity and specificity, operating at the live cell rather than DNA level. Specificity was demonstrated by controls performed in the presence of a 500× excess of non-pathogenic Lactococcus lactis . The system's versatility was demonstrated by its successful application to the detection and quantitation of Escherichia coli O157:H15 and Enterobacter cloacae . This new technology allows fast, low-cost, portable and automated bacteria detection for various applications in food, environment, security and clinics.